2019
DOI: 10.5004/dwt.2019.24430
|View full text |Cite
|
Sign up to set email alerts
|

Rhizomicrobial-augmented mature vetiver root system rapidly degrades phenol in illegally dumped industrial wastewater

Abstract: a b s t r a c tIllegal dumping of phenol-concentrated industrial wastewater in a residential area poses serious health risks to the community in Thailand. Thus, a low-cost and easily implementable treatment technique that the affected community can perform is greatly beneficial. Here, we evaluated the enhanced phenol-degradation kinetics using a rhizomicrobial-augmented mature vetiver root system on a floating platform (with and without aeration) in comparison to a previously published study of a young vetiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…3c), which is in good agreement with phytoremediation using vetiver for phenol degradation. 28 As the previous literature describes, 32 ORP is a vital indicator of the natural water condition, and a more negative ORP value corresponds to the better antioxidant properties of water. Accordingly, the ORP data in the current study implied that some reducing agents, like organic substances capable of being oxidized, might be produced during the cultivation of R. rotundifolia and released to the overlying water.…”
Section: Mechanism Discussion Based On Physiological Metabolismmentioning
confidence: 97%
See 1 more Smart Citation
“…3c), which is in good agreement with phytoremediation using vetiver for phenol degradation. 28 As the previous literature describes, 32 ORP is a vital indicator of the natural water condition, and a more negative ORP value corresponds to the better antioxidant properties of water. Accordingly, the ORP data in the current study implied that some reducing agents, like organic substances capable of being oxidized, might be produced during the cultivation of R. rotundifolia and released to the overlying water.…”
Section: Mechanism Discussion Based On Physiological Metabolismmentioning
confidence: 97%
“…The corresponding conclusions have been demonstrated in several previous studies. For instance, rhizomicrobes could rapidly degrade phenol in illegally dumped industrial wastewater, 27,28 indicative of the vital role rhizosphere microorganisms play in removing organic pollutants. In view of the synthetic wastewater used, however, the microbial diversity was not analyzed in the current study, yet it will be carried out in our ongoing experiments with real wastewater since the exploration on rhizomicrobial activities in real wastewater would be more meaningful.…”
Section: Nutrient Removal At Normal Temperaturementioning
confidence: 99%
“…These strategies encompass cheap, efficient, eco-friendly and solar-driven technologies with good public acceptance [7]. Several reports have been published pertaining to the use of plants such as vetiver root [8,9], alfalfa [10], willow trees [11] and the hairy roots of J o u r n a l P r e -p r o o f Helianthus annuus L. [5] for the remediation of phenol. Phenrat et al (2017) reported that phenol degradation by vetiver in real aerated wastewater involves two phases:…”
Section: Introductionmentioning
confidence: 99%
“…Phase I, phytoppolymerization and phyto-oxidation assisted by root-produced peroxide (H2O2) and peroxidase (POD), followed by phase II, similar to phase I with enhanced rhizomicrobial degradation [9]. Teeratitayangkul et al (2019) observed that maturation of plantlets results in an increase in the root biomass; this phenomenon results in both the release of increased levels of peroxidase and enhanced superoxide dismutase activity. The former occurrence accelerates phenol transformation, while the latter decreases the side effects associated with phenol detoxification [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation